THE METHODS FOR CALCULATION OF DECLINATION (D) FOR SPACED OF MAGNETIC OBSERVATORIES - Sokolova, O.I.; Mukasheva, S.N. (Academic Scientific Journal of Computer Science, 2020)
Calculations of the base values of the geomagnetic declination from the experimental data and from the data computed from various modern geomagnetic field models for spaced of geomagnetic observatories are presented: «Almatinskaya» (AAA) [43.25° N; 76.92° E] Institute of the Ionosphere, Almaty, Kazakhstan; «Kluchi» (NVS) of the Russian Academy of Sciences, Novosibirsk, Russia [54.85° N; 83.23° E]; «Irkutsk» (IRT) of the Institute of Solar-Terrestrial Physics of, Irkutsk, Russia [52.17° N, 104.45° E]. The characteristics of the results of the study of the time course and the spatial distribution of the values of the geomagnetic declination are given. The estimation of accuracy of calculation of geomagnetic declination by modern models of a geomagnetic field is presented. It is shown that the values of geomagnetic declination for spaced of geomagnetic observatories AAA, NVS, IRT from observed observational data change their values by years, so for AAA and NVS there is an increase, and for IRT the decrease in the values of geomagnetic declination. For NVS and AAA, geomagnetic declination moves eastward, and for IRT in the west. It is shown that the performed calculations of geomagnetic declination for two models International Geomagnetic Reference Field and World Magnetic Model for the coordinates AAA, NVS and IRT agree well with each other over the years, with small differences in seconds; the geomagnetic declination values for AAA increase in years with a gradient of about 0.6 min/year, for NVS decrease with a gradient of about 1.6 min/year, for IRT decrease with a gradient of about -4.5 min/year; model-calculated geomagnetic declination for AAA and NVS have an eastern direction, and for IRT, the western direction.